BAKTI SOSIAL PENYULUHAN DAN PEMERIKSAAN KESEHATAN GIGI DAN MULUT DALAM RANGKA HUT KE VI DD GROUP DI PAINAN - Nila Kasuma; Dewi Muarofah; Fajriah Fajriah; Hilda Lestari; Wita Wita; Haria Fitri; Fildzah Nurul Fajrin (Jurnal Pengabdian Warta Andalas, 2018)
Dental caries is the most common chronic disease of children. Caries is associated withpain and loss of teeth, as well as impaired growth, decreased weight gain, and negative effectson appearance, self-esteem, speech, and school performance. Therefore, oral health shouldalways be maintained. Healthy teeth results in comfort in talking, eating, drinking,and doingall primary activities that humans desperately need. Therefore, community service activities toimprove and care for dental and oral health at the national level. Through this dedication isexpected dentists can share knowledge to the community as a form of community service. The activities are form of cooperation between Faculty of Dentistry Andalas University andUniversity of North Sumatera alumnae. This service are held in SDN 19 South Painan consistof counseling, mass toothbrushing , and dental screening .